Molar Incisor Hypomineralisation: Current Knowledge and Practice - Helen D. Rodd; Anna Graham; Niecoo Tajmehr; Laura Timms; Noren Hasmun (Elsevier, 2021)
Background: Molar incisor hypomineralisation (MIH) is a common developmental dental condition that presents in childhood. Areas of poorly formed enamel affect one or more first permanent molars and can cause opacities on the anterior teeth. MIH presents a variety of challenges for the dental team as well as functional and social impacts for affected children. Objectives: Here, we provide an up-to-date review of the epidemiology, aetiology, diagnosis and clinical management of MIH. Materials and methods: A review of the contemporary basic science and clinical literature, relating to MIH, was undertaken using information obtained (up to 10 April 2020) from the electronic databases PubMed, Scopus, Web of Science and the Cochrane Library. Results: There is a growing body of evidence relating to the aetiology, presentation and clinical management of MIH. Current knowledge appears to be focused on potential genetic aspects, as well as the development and validation of indices for the diagnosis and management of MIH. There has also been increasing recognition of the global and individual burden of this common condition. Conclusions: Dental health professionals should regularly appraise the basic science and clinical MIH literature to ensure that they provide the best possible short- and long-term care for their young patients.